Tanaka Kinuyo : nation, stardom and female subjectivity - González-López, Irene; Smith, Michael (Michael James) (Edinburgh studies in East Asian film., 2018)
This is the first book in English dedicated to the actress and director Tanaka Kinuyo. Her career overlapped with a transformative period in Japanese history, and this close analysis of her fascinating life and work offers new perspectives, subjectivities and modes of analysis for the classical era of Japanese cinema.